THE INFLUENCE OF RELIGIOSITY, KNOWLEDGE, AND INCOME ON INDIVIDUALS' DECISIONS TO PAY ZAKAT, INFAQ, AND SADAQAH (ZIS) - Windiasari, Fica Afria; Rahayu, Yayuk Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to determine the influence of religiosity, knowledge, and income on the decision of muzaki to pay zakat, infaq, and sadaqah (ZIS) at BAZNAS Malang City. The research method is quantitative, using a survey approach and multiple linear regression analysis. Primary data were collected through questionnaires from 112 muzaki respondents of BAZNAS Malang City in 2023–2024. The results show that only the religiosity variable has a significant partial effect on the decision to pay ZIS. Meanwhile, knowledge and income do not show significant effects. However, simultaneously, all three variables influence the decision of muzaki to fulfill ZIS obligations. These findings emphasize the importance of spiritual aspects in encouraging zakat compliance through official institutions, as well as the need to optimize educational efforts and fundraising strategies that consider income factors.